ANALISIS PENGARUH HARGA, LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BUAH DAN SAYUR DI SUPERMARKET HOKKY PANGLIMA SUDIRMAN SURABAYA - Feby Anggita Prastiwi; Nuriah Yuliati; Dona Wahyuning Laily (Lampung University, 2023)
The level of consumption of fruit and vegetables per capita in a year in East Java has increased, but the level of consumption of fruit is still lower than vegetables. The emergence of fruit marketing companies, both supermarkets and shops, resulted in intense competition to overcome the increasing competition in seizing market opportunities. This study analyzes consumer characteristics and analyzes the effect of price, location, and product quality on fruit and vegetable purchasing decisions at Hokky Panglima Sudirman Supermarket Surabaya. This research was conducted at the Hokky Panglima Sudirman Supermarket, Surabaya. The sampling technique was accidental sampling with 80 respondents. The sample criteria used are consumers who buy fruit and vegetables at the Hokky Panglima Sudirman Supermarket, Surabaya. The analysis method uses SEM-PLS with the help of WarpPLS version 8.0 software. The results of this study indicate that price, location, and product quality have a positive and significant effect on fruit and vegetable purchasing decisions at Hokky Panglima Sudirman Supermarket SurabayaKey words: place, price, product quality, purchasing decisions, supermarket